Self-enforcing intergenerational social contract as a source of Pareto improvement and emission mitigation - Kerstin Burghaus; Thang Nguyen Dao; Ottmar Edenhofer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
We consider, in a general equilibrium overlapping generations (OLG) model with environmental externalities, a contract between successive generations, whereby agents of the current working-age generation privately invest a share of their labor income in pollution mitigation in exchange for a transfer to their old-age capital income paid by the next generation. We analyze under which conditions there exist contracts which are Pareto-improving compared to an equilibrium without contract and characterize the set of Pareto-improving mitigation-transfer combinations, the Pareto frontier and the Nash bargaining solution. Further, we prove that steady state emissions under a Pareto-improving contract are lower than without a contract. In the second part of the paper, we study a non-cooperative setting, taking into account that credibly committing to a contract might not be possible. We show that there exists mitigation transfer schemes which are both Pareto-improving and give no generation an incentive to deviate from the provisions of the contract.
Keywords: Q52; D70; C72; 330